MnSOD mediates shear stress-promoted tumor cell migration and adhesion - Ma, Shijun (2020)
Circulation of cancer cells in the bloodstream is a vital step for distant metastasis, during which cancer cells are exposed to hemodynamic shear stress (SS). The actions of SS on tumor cells are complicated and not fully understood. We previously reported that fluidic SS was able to promote migration of breast cancer cells by elevating the cellular ROS level. In this study, we further investigated the mechanisms regulating SS-promoted cell migration and identified the role of MnSOD in the related pathway. We found that SS could enhance tumor cell adhesion to extracellular matrix and endothelial monolayer, and MnSOD also regulated this process. Briefly, SS stimulates the generation of mitochondrial superoxide in tumor cells. MnSOD then converts superoxide into hydrogen peroxide, which activates ERK1/2 to promote tumor cell migration and activates FAK to promote tumor cell adhesion. Combining our previous and present studies, we present experimental evidence on the pro-metastatic effects of hemodynamic SS and reveal the underlying mechanism. Our findings provide new insights into the nature of cancer metastasis and the understanding of tumor cell responses to external stresses and have valuable implications for cancer therapy development.